Electrochemical reduction of nitrobenzene and 4-nitrophenol in the room temperature ionic liquid [C(4)dmim][N(Tf)(2)] - Silvester, D; Wain, A; Aldous, L; Hardacre, C; Compton, R (2006)
The reductions of nitrobenzene and 4-nitrophenol were studied by cyclic voltammetry in the room temperature ionic liquid 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide [C4dmim][N(Tf)2] on a gold microelectrode. Nitrobenzene was reduced reversibly by one electron and further by two electrons in a chemically irreversible step. The more complicated reduction of 4-nitrophenol revealed three reductive peaks (two irreversible and one reversible) which were successfully simulated using the digital simulation program DigiSim® using a mechanism of rapid self-protonation, given below.(1)HOC6 H4 NO2 + e ⇋ HOC6 H4 NO2{radical dot} -(2)Mathematical expression(3)Mathematical expression(4)HOC6 H4 NO2 H- + HOC6 H4 NO2 → HOC6 H4 NO + - OC6 H4 NO2 + H2 OTwo further anodic peaks were observed and were attributed to the oxidations of 4-hydroxyphenylhydroxylamine and 4-nitrophenolate respectively. For both nitrobenzene and 4-nitrophenol, diffusion coefficients were roughly two orders of magnitude smaller than in conventional solvents. It appears that both species are reduced following the same mechanisms as in conventional aprotic solvents, with differences in the voltammetry primarily due to the viscous nature of the ionic liquid. © 2006 Elsevier B.V. All rights reserved.